2019
DOI: 10.5860/crl.80.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Theses and Dissertations Programs: A Review of the Critical Success Factors

Abstract: An early version of this study has been presented in the 19th International Symposium on Electronic Theses and Dissertations (Lille, France). Our gratitude to the reviewers and participants of the ETD national policies session for their constructive feedback. Furthermore, we are grateful to Dr. Joachim Schöpfel (Université Lille 3) for his suggestions on an early version of this manuscript. Electronic Theses and Dissertations (ETDs) programs have been recognized as one of the most effective channels through wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…Similar findings by Abdul Rahman et al, (2020) incorporating Delone and McLean’s model and organizational support perspective found training and education, digital library environment and communication support, desire to use digital library services, net benefits, and user satisfaction as some of the critical success factors in the proper implementation and adoption of the use of digital library technologies by users. Besides, the content has been identified as an important component in implementing a digital library (Rasuli et al, 2019). In addition, Harinarayana and Raju (2010), Hart and Zinn (2007), and Kulenovic (2011) also argue that library personnel also needs proper and adequate training to empower its citizens with skills for active participation in society.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar findings by Abdul Rahman et al, (2020) incorporating Delone and McLean’s model and organizational support perspective found training and education, digital library environment and communication support, desire to use digital library services, net benefits, and user satisfaction as some of the critical success factors in the proper implementation and adoption of the use of digital library technologies by users. Besides, the content has been identified as an important component in implementing a digital library (Rasuli et al, 2019). In addition, Harinarayana and Raju (2010), Hart and Zinn (2007), and Kulenovic (2011) also argue that library personnel also needs proper and adequate training to empower its citizens with skills for active participation in society.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is essential that personnel handling digital library systems possess the technical competencies to enable their work to be carried out effectively, thus emphasising the importance of having technically skilled staff (Sonker and Mahawar, 2017) Information professionals managing digital libraries need to be knowledgeable in digitisation and the creation and management of metadata to assist them in preserving digital resources and managing information online (Raju, 2017) Process, a factor under the technology dimension, is the fourth CSF. Process is also a success factor in digital libraries of electronic theses and dissertations (Rasuli, Solaimani and Alipour, 2019) where the presence of unique identifier contributes to the success of digital library implementation. The implementation of Digital Object Identifier (DOI) ensures the identification of digital objects (Tiliute, 2016) It also provides a way to guarantee that digital copies of articles can remain accessible even if a journal changes its domain name or ceases publishing (Arms, Blanchi and Overly, 1997;Hume-Pratuch, 2014).…”
Section: Critical Success Factors For Digital Library Implementationmentioning
confidence: 99%
“…The researchers conducted a survey distributed to 354 repository managers worldwide and found the possibility of 46 variables under the six factors being important for the success of institutional repository implementation. In a systematic literature review of CSFs for DL of electronic theses and dissertations (ETDs), Rasuli et al (2019) identified 45 CSFs and conceptualised a generic framework comprising five dimensions: management and organisation, participation, content, technology and service for a DL of ETDs. The framework may help the ETDs practitioner community to make informed decisions on how to allocate effort and resources to the implementation and improvement of an ETDs programme.…”
Section: El 383mentioning
confidence: 99%
“…Factors and conditions that would bring about successful digital library (DL) implementation have been discussed in many studies (Gonçalves et al, 2007;Lagzian et al, 2015;Rasuli et al, 2019;Shen et al, 2006;Westell, 2006;Xia and Sun, 2007;Zuccala et al, 2008). Methodologies and techniques that have been adopted and adapted, applied and used by first adopters of DLs are considered essential for successful implementation of the systems worldwide.…”
Section: Introductionmentioning
confidence: 99%